Compensatory processes in solving social problems - Słaboń, Andrzej (Research on social problems in (pre-)pandemic reality, 2023)
The article considers the role of compensatory processes in the emergence and solution of social problems. Compensation is usually considered as compensating for deficits of various groups and social environments. Compensating for inequality through inclusion policies is becoming an essential feature of the welfare state. However, compensatory processes can be understood more broadly as the reactions of entities to the dominant features of the social order. In this context, spontaneous compensation is indicated. The manifestation of the dominant features of the social order is the phenomenon of excessive formalization and overregulation of social life leading to various forms of social opposition. The widely emphasized policy of inclusion produces opposite tendencies of the character of hidden exclusion. Solving many social problems in this approach consists in the conversion of spontaneous compensation processes. Regulating these processes becomes part of the positive social policy agenda.